The effects of cognitive distraction on behavioural, oculomotor and electrophysiological metrics during a driving hazard perception task. (April 2020) - Savage, Steven W.; Potter, Douglas D.; Tatler, Benjamin W.
Highlights: Effect of cognitive load was assessed on behavioral, eye movement and EEG metrics. Elements of the saccadic eye movement system can be used as markers of distraction. Eye fixation related potentials are sensitive to changes in cognitive workload. Markers of distraction were present prior to reduction in primary task performance. Abstract: Previous research has demonstrated that the distraction caused by holding a mobile telephone conversation is not limited to the period of the actual conversation (Haigney, 1995; Redelmeier & Tibshirani, 1997; Savage et al., 2013). In a prior study we identified potential eye movement and EEG markers of cognitive distraction during driving hazard perception. However the extent to which these markers are affected by the demands of the hazard perception task are unclear. Therefore in the current study we assessed the effects of secondary cognitive task demand on eye movement and EEG metrics separately for periods prior to, during and after the hazard was visible. We found that when no hazard was present (prior and post hazard windows), distraction resulted in changes to various elements of saccadic eye movements. However, when the target was present, distraction did not affect eye movements. We have previously found evidence that distraction resulted in an overall decrease in theta band output at occipital sites of the brain. This was interpreted as evidence that distraction results in a reduction in visual processing. The current study confirmed this by examining the effects of distraction on the lambda response component of subjects eye fixation related potentials ( EFRP s). Furthermore, we demonstrated that although detections of hazards were not affected by distraction, both eye movement and EEG metrics prior to the onset of the hazard were sensitive to changes in cognitive workload. This suggests that changes to specific aspects of the saccadic eye movement system could act as unobtrusive markers of distraction even prior to a breakdown in driving performance.